The Development of Industrial Work Practice Monitoring by Using “Simorin” at Vocational High School (Universitas Negeri Semarang, 2017)
Vocational High School graduates are expected to have work experience in industry and ready to enter the workforce. Industrial work practice (Prakerin) is a learning program that must be implemented by students in the industrial world. Prakerin program is organized together between school and the world of work to meet the students' need for competencies that are unworkable in schools. There are still major obstacles in monitoring the implementation of Prakerin due to distance and time problems. These constraints are expected to be solved using information system.This research and development aims to produce an effective and effective information system on industrial work practice monitoring to be used in vocational high school. This study developed information system named